Information Needs Of Goat Rearing Farmers In Mathura District - Sinha, S.K.; Chander, Mahesh; Mohan, Braj; K. , Pachaiyappan (Indian Journal of Veterinary Sciences and Biotechnology, 2016)
An ex-post-facto study was conducted to assess the information needs of goat rearing farmers as perceived by them, with a sample size of 160 respondents in Mathura district of Uttar Pradesh. Information needs were assessed in total 34 aspects of goat rearing practices; five each from health care and marketing-finance and eight each from breeding, feeding and housing-management. The investigation revealed that goat health care was the first area for information need as perceived by the farmers followed by marketing-finance, feeding, housing-management and breeding. Among specific sub areas; information regarding ‘common goat diseases with their preventive measures’, ‘vaccination’, ‘local market’, ‘banking finance for goat farm’, ‘preparation of economic and balanced ration’, ‘care of does’ and ‘breed selection’ were perceived with higher intensity of need.